2018
DOI: 10.3892/mmr.2018.9246
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA UCA1 promotes papillary thyroid cancer cell proliferation via miR‑204‑mediated BRD4 activation

Abstract: Long non‑coding RNA (lncRNA) urothelial carcinoma‑associated 1 (UCA1) has been used in tumor development and progression in many types of cancer. However, the function and mechanism underlying the action of UCA1 in papillary thyroid cancer (PTC) remains unclear. Therefore, these topics were investigated in the present study by in vitro and in vivo experiments. It was demonstrated that the expression level of UCA1 was more significantly upregulated in PTC cell lines and tissues when compared with the immortal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…32 Two other studies also indicated the role of UCA1 in stimulating proliferation of PTC cells. 33,34 In line with these previous studies, we found that UCA1 was upregulated in PTC tissues and associated with prognosis by public data investigation. To further explore the clinical significance of UCA1 in PTC, qRT-PCR analysis was performed to determine UCA1 expression levels in PTC tissue, adjacent noncancerous control tissues, and metastatic cervical lymph nodes.…”
Section: Discussionsupporting
confidence: 88%
“…32 Two other studies also indicated the role of UCA1 in stimulating proliferation of PTC cells. 33,34 In line with these previous studies, we found that UCA1 was upregulated in PTC tissues and associated with prognosis by public data investigation. To further explore the clinical significance of UCA1 in PTC, qRT-PCR analysis was performed to determine UCA1 expression levels in PTC tissue, adjacent noncancerous control tissues, and metastatic cervical lymph nodes.…”
Section: Discussionsupporting
confidence: 88%
“…It was found that UCA1 significantly promoted proliferation and migration of thyroid cancer cells; the underlying mechanism was that UCA1 competed with c-myc proto-oncogene (c-myc) for miR-135a binding [84]. Similarly, UCA1 promoted growth and invasion of papillary thyroid carcinoma by competing with bromodomain containing 4 (BRD4) or insulin-like growth factor-binding protein 5 (IGFBP5) for miR-204 binding [85,86].…”
Section: Thyroid Cancermentioning
confidence: 99%
“…Among these lncRNAs involving in the ceRNA network, Li et al have reported that Linc00483 acting as ceRNA regulated proliferation and apoptosis via activating mitogen‐activated protein kinases in gastric cancer. In addition, recent studies indicated that lncRNA UCA1 played important roles in the progression of various cancers, including papillary thyroid carcinoma, melanoma, esophageal squamous cell carcinoma, and breast cancer . In the previous study, HULC could act as an oncogene through negatively regulating miR‐125a‐3p in ovarian carcinoma .…”
Section: Discussionmentioning
confidence: 92%
“…In addition, recent studies indicated that lncRNA UCA1 played important roles in the progression of various cancers, including papillary thyroid carcinoma, melanoma, esophageal squamous cell carcinoma, and breast cancer. [38][39][40][41] In the previous study, HULC could act as an oncogene through negatively regulating miR-125a-3p in ovarian carcinoma. 42 Importantly, lncRNA HULC, which was activated by oxidative stress, could enhance CCA cellular migration and invasion by a ceRNA mechanism.…”
Section: Discussionmentioning
confidence: 99%